2022
DOI: 10.1002/pits.22707
|View full text |Cite
|
Sign up to set email alerts
|

Parental marital conflict, negative emotions, phubbing, and academic burnout among college students in the postpandemic era: A multiple mediating models

Abstract: Given the serious effects of coronavirus disease 2019 on academic burnout, this study aims to examine the multiple mediating roles of negative emotions and phubbing in the relationship between parental marital conflict and academic burnout. A total of 1353 college students participated in this study. The results showed that parental marital conflict not only had a direct effect on academic burnout but also affected academic burnout through three indirect paths: parental marital conflict‐negative emotions‐acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(69 reference statements)
0
9
1
Order By: Relevance
“…There are two possible reasons for this result. First, marital conflict is a negative experience for children in the family, and the negative emotions generated by such experiences can lead to addictive behaviors [ 70 ]. Second, parental care and warmth are important resources for child growth.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible reasons for this result. First, marital conflict is a negative experience for children in the family, and the negative emotions generated by such experiences can lead to addictive behaviors [ 70 ]. Second, parental care and warmth are important resources for child growth.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have investigated the association between psychological distress and academic burnout but reached the opposite conclusion. Smith and Emerson (2021) have indicated that academic burnout and its dimensions had effects on psychological distress, whereas other scholars thought that negative emotions worsened academic burnout (Salmela-Aro et al, 2009;Zhang et al, 2022). Existing research, however, has primarily focused on college students, and this relationship among junior high school students was not well explored.…”
Section: The Role Of Psychological Distressmentioning
confidence: 99%
“…Although there is no direct evidence to support the relationship between psychological distress and phubbing behavior, indirect evidence can be obtained by examining research on adjacent concepts. For example, previous studies have found that negative emotion (e.g., stress, anxiety, and depression) is an important predictor of phubbing (Davey et al, 2018; Zhang et al, 2022). When parental burnout is high, children may experience a higher level of psychological distress, which may in turn lead to more phubbing behaviors.…”
Section: Introductionmentioning
confidence: 99%